Membangun Harmoni Spiritual dan Ekologis: Perspektif Tasawuf terhadap Krisis Lingkungan di Sungai Luk Ulo: Perspektif Tasawuf terhadap Krisis Lingkungan di Sungai Luk Ulo - Laksono, Gangsar Edi; Afifaturrifani; Waliko; Setyowati, Putri Ratna (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
The Luk Ulo River in Central Java, Indonesia, faces severe ecological degradation due to unregulated sand mining activities, threatening its biotic, abiotic, and socio-economic functions. This study examines the environmental crisis from a spiritual-ecological lens by integrating Sufi perspectives within Islamic environmental ethics. Using a qualitative descriptive approach based on an extensive literature review, the research explores the potential of tasawuf ekologis (ecological Sufism) as a transformative framework to rebuild the spiritual connection between humans and nature. The findings reveal that current legal and technical approaches remain insufficient in addressing the root causes of ecological destruction, which are deeply tied to human disconnection from spiritual values. Core Sufi principles such as zuhud (asceticism), muraqabah (spiritual vigilance), and rahmah (compassion) offer an ethical foundation for sustainable environmental stewardship. This study recommends integrating eco-theological education, promoting community-based sustainable livelihoods, and engaging religious leaders as agents of change. The proposed approach positions ecological Sufism not only as a moral paradigm but also as a culturally resonant strategy for grassroots ecological transformation. Future empirical research is needed to assess community reception and practical implementation of this spiritual-environmental model across diverse ecological settings.